Muonium diffusion in solid CO2: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Eshchenko, D. G.; Storchak, V. G.; Brewer, J. H.; Cottrell, S. P.; *, S. F. J. Cox (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The quantum diffusion of interstitial muonium atoms in solid CO2 is studied in the temperature range from 5 to 200 K using the technique of muonium spin rotation and relaxation. Muonium exhibitscoherent bandlike dynamics between 140 and 160 K. At low temperature Mu undergoes stronglocalization.